Exploring referee abuse through the lens of the collegiate rugby coach. Issue 1 (February 2020) - Jacobs, Brittany L.; Tingle, Jacob K.; Oja, Brent D.; Smith, Mark A.
Highlights: Need for exploring referee abuse through lens of non-referees. Coaches believe they can play an active role in elimination of referee abuse. Rugby coaches suggest five factors influence their perceptions of abuse. Consideration of interventions from the interpersonal to cultural levels may be valuable. Abstract: Referees are valuable contributors to the legitimacy of a sporting contest. Despite this, abuse in sport has become a growing concern and is regularly noted as an obstacle with which referees must contend. Continued abuses have been associated with referee discontinuation and have been noted as a detrimental influence in the recruitment and retention of referees. Sporting organizations, coaches, and players all feel the impact when there is an inadequate supply of referees. Coaches have been noted as a primary perpetrator of referee abuse; thus, in this study, the authors utilize a phenomenological approach to explore perceptions of referee abuse through the lens of the collegiate rugby coach. Data were collected from 15 participants, all of whom completed two phone interviews. Five factors that influence one's perceptions of and proclivity towards referee abuse emerged from the data: (a) personal characteristics/philosophies, (b) relationships, (c) social influences, (d) organizational expectations, and (e) culture. Implications to practice and recommendations for future research are discussed.